SOLUSI BERBASIS TEKNOLOGI UNTUK PENCEGAHAN STUNTING: KOMBINASI VIRTUAL NUTRI MENTOR BERBASIS AI DAN PROGRAM MAKAN BERGIZI GRATIS UNTUK KELUARGA RENTAN (BAPPEDA Kota Tangerang, 2024)
Introduction: Stunting, a chronic health issue stemming from prolonged malnutrition within the first 1,000 days of life, affects 22.3% of children globally under the age of five, resulting in considerable physical and cognitive impairments. In Indonesia, the prevalence of stunting was 21.6% in 2023, particularly affecting vulnerable regions such as Tangerang. Objective: This study seeks to integrate an AI-powered Virtual Nutri Mentor with free nutritious meal programs to combat stunting in vulnerable families. Methods: By employing Agile Methodology, an AI-based chatbot was created to deliver personalized nutrition advice via WhatsApp. This iterative approach facilitated ongoing system refinement based on user feedback. Results: The AI-driven Virtual Nutri Mentor provided customized dietary recommendations, which bolstered the effectiveness of community-level free meal programs. Conclusion and Recommendation: The integration of AI technology with traditional interventions offers a scalable solution for stunting prevention. Future research should focus on long-term monitoring and the expansion of this approach to other vulnerable regions.